Termination And Consequences Of Ear Farms In The Districts Of Fergana, Tashkent, Samarkand. (Eurasian Journal of Humanities and Social Sciences, 2023)
This article outlines land and water reform in the Central Asian republics, which are part of the Soviet Union, in the provinces of Fargo, Tashkent, and Samarkand